A 8.5 to 11.6 GHz digitally controlled variable gain amplifier with 15‐dB gain range and 1‐dB step. Issue 2 (29th August 2020) - Wu, Tianjun; Zhang, Xiaoning; Xing, Zhao; Zhao, Chenxi; Yu, Yiming; Liu, Huihua
Abstract: A X‐band variable gain amplifier (VGA) with low phase variation and high control resolution is presented in 180‐nm CMOS. The linear gain VGA and current‐type digital‐to‐analog converter (DAC) are implemented to improve the accuracy of gain control and the robustness against process, supply voltage, and temperature variations (PVT). The measured peak gain and 3‐dB bandwidth are 8 dB and 8.5 to 11.6 GHz, respectively. The gain range is 15 dB with a gain step of 1 dB. With a supply voltage varying from 1.6 to 2.0 V, the root‐mean‐square (RMS) gain and phase errors in 3‐dB bandwidth are <0.62 dB and <1.5°, respectively. With supply of 1.8 V, the measured root‐mean‐square (RMS) gain and phase errors across −25 to 110°C are <0.65 dB and <1.7°, respectively. Comparing the measurement results of five chips, the variation of RMS gain error is <0.24 dB, and the RMS phase errors are almost the same. The measurement results demonstrate the proposed VGA is very suitable for phased arrays in X‐band.